On the mechanisms of tip-force induced switching in ferroelectric thin films: the crossover of depolarization, shear strain and flexoelectricity. (13th February 2019) - Ma, L L; Chen, W J; Liu, Y L; Wang, Biao; Zheng, Yue
Abstract: The recent observation of mechanical switching of ferroelectric polarization has placed the mechanical manipulation of ferroelectrics on an equal footing with the conventional electrical manipulation. However, discussions on the exact switching mechanisms due to mechanical loads are ongoing for the complexity in experimental situations. In this work, based on continuum mechanical and thermodynamic modeling and simulation, we analyze the mechanisms of tip-force induced switching in ferroelectric thin films. The roles of depolarization, shear strain and flexoelectricity in mechanical switching, both in normal and sliding loading modes, are separated out and the switching characteristics are analyzed. The depolarization field in the film is demonstrated to enable bidirectional switching. The coupling between shear strain and polarization components is shown to be important in the sliding loading mode. A great influence of flexoelectricity-modified polarization boundary condition on the switching process is revealed. The previous speculation that the switching process experiences an intermediate paraelectric phase is proved. The regulation of loading force, misfit strain, temperature and film thickness on the switching are further given for each mechanism. Taking all of the three mechanisms into account, we present the phase diagrams of mechanical switching for films in an initial upward or downward polarization state. The revealed characteristics of various switching mechanisms should provide useful guidelines for their verification in experiments, and the tunability of the switching by various influencing factors is instructive for the design and optimization of ferroelectric devices via mechanical engineering.